(untitled) (Journal of Telenursing (JOTING), 2025)
This study aimed to analyze the relationship between fasting duration, type of anesthesia, and surgical duration with the incidence of thirst in pre-anesthetic patients at Welas Asih Regional General Hospital, West Java Province. The method used was an observational analytic approach with a cross-sectional approach. The results showed that the majority of respondents were female (58.8%), with the highest fasting duration being 6–8 hours (64.7%), mild thirst intensity (54.1%), and no signs of dehydration (81.2%). Statistical tests showed a significant association between fasting duration (p=0.018; OR=2.45) and surgical duration (p=0.043; OR=1.97) with thirst intensity. While the type of anesthesia had no effect (p=0.214). In conclusion, fasting duration and surgical duration influence the intensity of thirst in pre-anesthetic patients, while the type of anesthesia has no effect. Keywords: General Anesthesia, Surgical Duration, Pre-anesthetic Fasting, Thirst